The Influence of Principal’s Supervision on the Performance of High School Teachers - Satin, Sumiani (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This research aims to determine the effect of principal supervision on teacher performance at SMA Negeri 1 Tanjung Lago, Banyuasin Regency. The method used in this research is a quantitative approach method which contains two variables, namely principal supervision (X1) and teacher performance (Y). Data was obtained through a questionnaire distributed to teachers at SMA Negeri 1 Tanjung Lago and analyzed using simple linear regression statistical techniques. The research results show that supervision carried out by the school principal has a significant influence on teacher performance. Effective supervision, including aspects of monitoring, evaluation and guidance, has been proven to be able to improve the quality of teaching and teacher professionalism. These findings indicate that the active role of school principals in carrying out supervision is very important to support improvements in teacher performance and, ultimately, the quality of education in the school. This research recommends that school principals intensify constructive and sustainable supervision activities to create an optimal learning environment.